A data-driven framing of player and team performance in U.S. Women's soccer - Narayanan, Sachin; Pifer, N. David (Frontiers in Sports and Active Living, 2023)
Introduction In establishing historical benchmarks for success on the pitch and striving to achieve parity off it, the United States Women's National Team (USWNT) and the National Women's Soccer League (NWSL) have long served as standard bearers for professional women's soccer around the globe. However, off-field dilemmas and incessant juxtapositions to men's soccer frequently overshadow the elements that make U.S. women's soccer unique; that is, in the quest to expose and rid the women's game of blatant misconduct, discriminatory practices, and negative stereotypes, relatively little attention has been devoted to performance features that separate the U.S. women's soccer product from its competition. Because many of the issues hindering the progress of women's soccer are rooted in media and managerial practices that marginalize or ignore its positive traits, a need exists for analyses that will properly identify its innate characteristics and competitive advantages so that media members, managers, and fans can accurately frame their perceptions of women competing in the sport. Methods To this end, we collected reliable samples of public event data from 560 professional soccer matches and used ANOVAs and t-tests to identify the characteristics that distinguish U.S. women's soccer from other professional leagues and teams. Results and Discussion In doing so, we showed that the USWNT tends to shoot from more opportune areas and press opponents at a higher rate, and that the NWSL has recently been matched in quality across certain performance metrics by England's FA Women's Super League.